Nitric oxide levels and antioxidant enzyme activities in jaundices of premature infants - Kilic, M; Turgut, M; Taskin, E; Cekmen, M; Aygun, AD (Wiley, 2004)
Free radicals are effective in the genesis of several diseases in the neonatal period. This study aimed to show the relationship between serum bilirubin levels and plasma nitric oxide and the activity of enzymes in the erythrocyte such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in premature infants. In the study, 20 premature infants with newborn jaundice were included and the control group was formed by 15 premature infants without jaundice. Venous blood samples were taken from all neonates in the study and control groups on the first day of hospitalization. Plasma nitric oxide levels and activities of SOD, GSH-Px and CAT enzymes in the erythrocytes were investigated in these samples. Plasma nitric oxide and serum bilirubin levels were found to be significantly higher in the study group (47.4 +/- 7.25 mumol l(-1), 18.41 +/- 3.28 mg dl(-1), respectively) than those in the control group (33.46 +/- 6.43 mumol l(-1), 4.35 +/- 0.60 mg dl(-1), respectively; p < 0.001). In addition, erythrocyte SOD, GSH-Px and CAT enzyme activities (724 +/- 78.61, 673 +/- 90.5, 63 +/- 12.8 U g(-1) Hb, respectively) were found to be significantly lower in the study group than those in the control group (1208 +/- 129.04, 1097.6 +/- 75.8, 99.06 +/- 12.4 U g(-1) Hb, respectively, p < 0.001). It was concluded that in the aetiology of hyperbilirubinemia, neonatal erythrocytes and nitric oxide reactions are affected differently and that erythrocyte haemolysis caused as a result of these effects may play a role in the aetiopathogenesis of unconjugated hyperbilirubinemia. Haemolysis may also be seen because of the inadequacy of the protection by erythrocytes against the cytotoxic effects of free radicals resulting from the lack of antioxidant enzymes in these cells. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: premature infant; hyperbilirubinemia; nitric oxide; antioxidant enzymes